FRI0267 Characterisationof the molecular profile of altered genes and pathways in monocytes of antiphospholipid syndrome patients related to their atherothrombotic status. effects of in vivo ubiquinol supplementation. (12th June 2018) - Perez-Sanchez, C.; Aguirre, M.A.; Perez-Sanchez, L.; Luque-Tevar, M.; Barbarroja, N.; Ruiz-Limon, P.; Jimenez-Gomez, Y.; Arias de la Rosa, I.; Abalos, M.C.; Segui, P.; Villalba, J.M.; Collantes, E.; et al.
Abstract : Objectives: This study was undertaken to: 1. Characterise monocytes molecular profile of altered genes and pathways involved in the pathology of APS. 2. To evaluate the role of antiphospholipid antibodies in the regulation of these processes. 3. To investigate the short-term effects of in vivo ubiquinol (reduced coenzyme Q10 [Qred]) supplementation on the modulation of genes related to inflammation and thrombosis in this autoimmune disorder. Methods: Monocytes from peripheral blood of 60 subjects, including 30 APS patients and 30 healthy donors (HDs) were purified by negative immunomagnetic selection (Miltenyi). Total RNA was extracted from 6 subjects –as exploratory cohort- and microarray studies were performed in an Agilent G4112F platform (Whole Human Genome Microarray 44 k). Functional categorization of the altered gene signature and molecular pathways and networks was carried out using the Ingenuity Pathway Analysis Software (IPA). The most differentially expressed genes were validated by RT-PCR in monocytes purified from all the subjects recruited to the study. Correlation and association studies were performed with clinical and analytical variables. The effects of antiphospholipid antibodies (aPL) were also evaluated by in vitro studies. The short-term effects of in vivo Qred supplementation on the monocyte gene profile were further analysed. Results: Gene expression array identified 518 altered genes in monocytes from APS patients in relation to the control group (p<0, 05 and fold change >2). IPA analysis showed that the main canonical pathways integrated by these genes were leukocyte adhesion, diapedesis and extravasation signalling, interleukin and cytokine signalling, as well as oxidative stress production and antioxidant response. This analysis further identified that the most relevant diseases in which these altered genes are involved were inflammatory and cardiovascular diseases (44%), as well as reproductive (42%), neurological (11%), renal (1%) and ophthalmic diseases (2%). The alteration of several of these genes was validated by RT-PCR and protein analysis, and associated to clinical parameters of APS patients, including thrombotic recurrences and early atherosclerosis. In vitro studies demonstrated the specific modulation of several genes by direct effect of aPLs. In vivo Qred supplementation of APS patients for one month significantly improved the monocytes' atherothrombotic gene profile, reversing the altered expression of a number of genes related to thrombosis, atherosclerosis, inflammation, oxidative stress, and intracellular signalling. Conclusions: 1. Gene expression profile allowed the identification of relevant genes and pathways altered in monocytes of APS patients, which are associated with the pathogenesis of the disease and modulated, at least partially, by aPLs. 2. We have branded novel and specific mRNAs related to CVD in APS monocytes, further modified by effect of in vivo Qred supplementation. Acknowledgements: Funded by JA (CTS-7940) and Ministry of Health (ISCIII, PI15/01333 and RIER RD16/0012/0015) cofinanced with FEDER funds. Disclosure of Interest: None declared